Neuroergonomics: a review of applications to physical and cognitive work - Mehta, Ranjana K.; Parasuraman, Raja (Frontiers in Human Neuroscience, 2013)
Neuroergonomics is an emerging science that is defined as the study of the human brain in relation to performance at work and in everyday settings. This paper provides a critical review of the neuroergonomic approach to evaluating physical and cognitive work, particularly in mobile settings. Neuroergonomics research employing mobile and immobile brain imaging techniques are discussed in the following areas of physical and cognitive work: 1) physical work parameters; 2) physical fatigue; 3) vigilance and mental fatigue; 4) training and neuroadaptive systems; and 5) assessment of concurrent physical and cognitive work. Finally, the integration of brain and body measurements in investigating workload and fatigue, in the context of mobile brain/body imaging ('MoBI'), is discussed.